Perancangan dan Evaluasi Media Bimbingan Karier: Efektivitas dan Kepraktisan Buku Ilustrasi Karier untuk Anak Prasekolah - Awanda Erna; Abdullah Sinring; Akhmad Harum (ILIN Education Indonesia, 2025)
This research is the development of career guidance illustration book media. The aim of this research is to find out: (1) An overview of the development of career illustration book guide media to introduce careers to children, (2) A prototype of the development of career illustration book guide media to introduce careers to children 3) The degree of validity and usefulness of the career illustration book guide for media growth. The present study used a modified version of the Borg and Gall development model, comprising seven stages: preparatory research and data collection, development planning, preliminary product creation, expert validation, first product revision, small-group field testing, and second revision. Questionnaires and interviews were employed as data gathering methods. The results of the research show that the description of the need for developing guidance media for career illustration books for introducing careers to children shows that there is a great need for guidance media as an information service for career introductions for children in the Passikolaan Enrekang Community. The career illustration book guidance media prototype consists of 10 main displays, namely the cover page, initial section and foreword as well as general objectives, instructions and steps for use, display of the main section, topics and expected objectives, song display, child readiness, display of material content, display final and evaluation section, evaluation task display, and author's biodata display. After the validation test was completed, the level of validity and practicality of the career illustration book guidance media was determined. The results of the material expert validation test were 82.5%, indicating that it is in line with children's needs, and the media experts scored 93.7% in terms of design and graphics, very good and for practicality The media was declared practical with a result of 95%, and was field tested by 8 children aged 5-6 years, the results were obtained with very valid criteria so that the career guidance media illustration book was declared worthy of being tested widely.